Altered brainstem pain-modulation circuitry connectivity during spontaneous pain intensity fluctuations - Mills, E.P.; Alshelh, Z.; Kosanovic, D.; Di Pietro, Flavia; Vickers, E.R.; Macey, P.M.; Henderson, L.A. (2020)
Background: Chronic pain, particularly that following nerve injury, can occur in the absence of external stimuli. Although the ongoing pain is sometimes continuous, in many individuals the intensity of their pain fluctuates. Experimental animal studies have shown that the brainstem contains circuits that modulate nociceptive information at the primary afferent synapse and these circuits are involved in maintaining ongoing continuous neuropathic pain. However, it remains unknown if these circuits are involved in regulating fluctuations of ongoing neuropathic pain in humans.